Modulus of Laterally Loaded Pile in Cohesionless Slope Crest with Varying Condition - Sivapriya, Vijayasimhan; Ganesh, Kumar Shanmugam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Soil - structure interaction behaviour of pile foundation is complex for heavier structures which suffer large lateral load due to wind, wave action etc., in addition to the large vertical and oblique load. The parameters involved in determining the lateral capacity of the foundation are its structural geometry, soil properties and ground condition. The behaviour is different for horizontal ground compared to the sloping ground; it is even different under loading and unloading conditions. In this study, the modulus of single pile is studied under various lengths, diameters, slope angles and loading directions. An equation is generated is developed to obtain the modulus with varying length and diameter.
Keywords: pile foundation; soil-structure interaction; lateral load; vertical load; fundament palowy; interakcja gleba-struktura; obciążenie boczne; obciążenie pionowe